2017
DOI: 10.1093/annonc/mdx119
|View full text |Cite
|
Sign up to set email alerts
|

Primary tumor sidedness has an impact on prognosis and treatment outcome in metastatic colorectal cancer: results from two randomized first-line panitumumab studies

Abstract: BackgroundPrevious studies have reported the prognostic impact of primary tumor sidedness in metastatic colorectal cancer (mCRC) and its influence on cetuximab efficacy. The present retrospective analysis of two panitumumab trials investigated a possible association between tumor sidedness and treatment efficacy in first-line mCRC patients with RAS wild-type (WT) primary tumors.Materials and methodsData from two randomized first-line panitumumab trials were analyzed for treatment outcomes by primary tumor side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
158
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(175 citation statements)
references
References 25 publications
13
158
2
2
Order By: Relevance
“…42,43 Primary tumour right-sidedness and mutant RAS status have been reported as unfavourable prognostic factors. 20,21,23,46 We observed that wild-type RAS status was strongly associated with CLM conversion to resectability by oxaliplatin-HAI. 20,21,23,46 We observed that wild-type RAS status was strongly associated with CLM conversion to resectability by oxaliplatin-HAI.…”
Section: Discussionmentioning
confidence: 81%
“…42,43 Primary tumour right-sidedness and mutant RAS status have been reported as unfavourable prognostic factors. 20,21,23,46 We observed that wild-type RAS status was strongly associated with CLM conversion to resectability by oxaliplatin-HAI. 20,21,23,46 We observed that wild-type RAS status was strongly associated with CLM conversion to resectability by oxaliplatin-HAI.…”
Section: Discussionmentioning
confidence: 81%
“…23 , 24 Right-sided tumours, often defined as proximal to the splenic flexure, are generally poorly differentiated, diagnosed in more advanced tumour stages, displaying different molecular patterns, and carrying a poorer prognosis than left-sided tumours. 24 , 25 Several studies also demonstrate the importance of taking PTL into account when evaluating treatment response, 26-28 and retrospective analyses from large phase III trials have demonstrated that patients with right-sided tumours have less benefit from the addition of EGFR-targeted therapy. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Overall survival (OS) after liver resections has been shown to be related to | 531 DUELAND Et AL. [5][6][7][8][9] Liver transplant (LT) is the standard of care for selected patients with malignant liver tumors such as hepatocellular carcinoma (HCC) and liver metastases from low-grade neuroendocrine tumors. About 20% of the patients with CRLMs are candidates for liver resections, 3 but about 60% to 70% have recurrence within 3 years.…”
Section: Introductionmentioning
confidence: 99%